Effect of Dose and Compound Fertilizer on Growth and Results of Red Chili - Burlian Hasani; Fitri Yetty Zairani (Journal of Global Sustainable Agriculture, 2021)
Effect of Dose and compound Fertilizer on the Growth and Yield of Hot Pepper plant (Capsicum annum, L.). This study aims to determine the effect of Formula Application and dosage of complete compound fertilizer on the growth and yield of chili plants. This study used a factorial Randomized Block Design (RAK) with nine treatment combinations and three replications, each treatment consisting of 3 plants. The combination of these treatments used two Complete Compound Fertilizer Formulas (P). Formula 1 (P1) Complete Compound Fertilizer Pril (PMLP), 2 (P2) : Complete Compound Fertilizer Tablets (PMLT), and 3 (P3) as a control mixture of single fertilizer Urea, SP 36, and KCL ( 1:1:1). The second formula is fertilizer dosage (D) which consists of three levels, namely D1 (30 g fertilizer/plant), D2 (40 g fertilizer/plant), and D3 (50 fertilizer/plant). The variables observed in this study were plant height, number of fruit per plant, fruit weight per plant, dry weight of plant stover. Based on the results of the research that has been carried out, it is concluded that the treatment of Complete Compound Fertilizer Formula (P) has a very significant effect on all observed variables, namely: plant height, number of fruits per plant, the weight of dry root, and weight of fruit per plant. While the Fertilizer Dosage (D): 30, 40, and 50 g did not show a significant difference in the results for all observed variables, and the interaction between the two did not show significant differences in all observed variables.